Status of the palliative care education in surgical postgraduate curriculum – implications for Pakistan - Qamar Riaz; Muhammad Rizwan Khan (Journal of the Pakistan Medical Association, 2020)
Palliative care has gained considerable attention during last few decades. Increasing demands by the society owing to increased number of elderly and people with chronic illnesses require increased number of health care professionals with competence in providing palliative care. The current review provides a summary of the published literature pertaining to palliative care education in surgical residency programmes internationally and locally. Most surgical residency programmes provide limited, if any, formal education in knowledge and skills related to palliative and end of life care. The situation is alarming in Pakistan where the discipline is in infancy and resources are limited while the demand for palliative care is increasing. Surgery can learn lessons from other disciplines. Development and integration of palliative medicine into most of the existing postgraduate curricula continues to be a challenge for the accreditation bodies and medical educationists. Continuous...